Mode of gavage feeding: does it really matters - Ambey, Ravi; Gogia, Priya; Manager, Kalpesh (International Journal of Contemporary Pediatrics, 2018)
Background: The establishment of safe oral feeding in preterm or low birth weight infants may be delayed because of poor co-ordination of sucking and swallowing, neurological immaturity and respiratory distress. Enteral feeds may be delivered through a catheter (feeding tube) passed via the nose or via the mouth. This study was planned to compare oro-gastric and naso-gastric route for placing feeding tube to see duration to achieve full feeding. Methods: The study was conducted in in-patient of SCNU (Sick Newborn Care Unit) of Department of Paediatrics. All patients (200 newborns) in the study were randomly enrolled in groups as per gestational weeks between 28-34 weeks by using New Ballard Scoring (NBS) chart at the time of admission. Results: The mean duration to achieve full feeding either by direct breast feeding or cup feeding in oro-gastric and naso-gastric tube groups are (6.18±0.61) and (6.47±0.59) days respectively. This study will help in the individualization of the mode of gavage feeding in various institutions across the country. Conclusions: In the present study the episodes of non-intentional removal and displacement are more in OGT group and it is statistically significant (p = 0.012 and p <0.0001 respectively). The episodes of feed intolerance are more.